2017
DOI: 10.1186/s12894-017-0234-2
|View full text |Cite
|
Sign up to set email alerts
|

Toileting behaviors and overactive bladder in patients with type 2 diabetes: a cross-sectional study in China

Abstract: BackgroundOveractive bladder is more prevalent in patients with type 2 diabetes than in those without diabetes. Unhealthy toileting behaviors may be associated with the development and worsening of overactive bladder symptoms. However, little is known about the relationships between toileting behaviors and overactive bladder in patients with diabetes. This study aimed to identify unhealthy toileting behaviors that patients with type 2 diabetes adopted to empty their bladders and investigate the relationships b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 38 publications
0
21
0
1
Order By: Relevance
“…More than half of female nurses often or always delayed emptying their bladders when they were busy and nearly half often or always waited more than 4 hr to urinate (Xu et al., ). Previous studies have found that unhealthy toileting behaviours were associated with bladder symptoms in female nurses (Wan et al., ), female advanced practice providers (Palmer & Newman, ), employed women at a large academic medical center (Palmer, Willis‐Gray, Zhou, Newman, & Wu, ) and patients with type 2 diabetes (Xu et al., ). Long‐term suppression of the urge to void may result in an enlarged bladder as a result of stretching to hold a larger capacity of urine than usual; this contributes to eventual bladder dysfunction (Fitzgerald, ; Kirkland, Palmer, & Fitzqerald, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…More than half of female nurses often or always delayed emptying their bladders when they were busy and nearly half often or always waited more than 4 hr to urinate (Xu et al., ). Previous studies have found that unhealthy toileting behaviours were associated with bladder symptoms in female nurses (Wan et al., ), female advanced practice providers (Palmer & Newman, ), employed women at a large academic medical center (Palmer, Willis‐Gray, Zhou, Newman, & Wu, ) and patients with type 2 diabetes (Xu et al., ). Long‐term suppression of the urge to void may result in an enlarged bladder as a result of stretching to hold a larger capacity of urine than usual; this contributes to eventual bladder dysfunction (Fitzgerald, ; Kirkland, Palmer, & Fitzqerald, ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study found that unhealthy toileting behaviours such as delayed voiding, straining to void and premature voiding were positively associated with lower urinary tract symptoms among female nurses (Wan et al., ). Another recent study found that premature voiding and straining to void may contribute to the onset or worsening of OAB in patients with type 2 diabetes (Xu et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors located one randomized controlled trial (RCT), one repeated measures study, three methodological studies, three qualitative studies (i.e., semi structured interviews and focus groups), and 17 cross-sectional studies. Seven studies reported using online questionnaires [7,8,9,10,11,12,13], 14 used a field survey or postal delivered questionnaire [2,3,14,15,16,17,18,19,20,21,22,23,24,25], and one study combined both a field survey and online questionnaire to collect information [26]. Three studies used uroflowmetry and sonography to measure multiple uroflowmetric parameters (e.g., maximum flow rate, Qmax and average flow rate, and Qave) and used postvoid residual (PVR) urine volume as one of the outcomes [14,15,21]; see Table S2 for an overview of the studies reviewed.…”
Section: Resultsmentioning
confidence: 99%
“…16 V Ve er ri i T To op pl la am ma a A Ar ra aç çl la ar rı ı: : Verilerin toplanmasında araştırmacılar tarafından literatür doğrultusunda geliştirilen tanıtıcı özellikler formu ve 18 maddeden oluşan TD-KBD Ölçeği kullanıldı. 11,18,19 T Ta an nı ıt tı ıc cı ı Ö Öz ze el ll li ik kl le er r B Bi il lg gi i F Fo or rm mu u: : Hemşirelerin yaş, cinsiyet, medeni durumları, meslekte toplam çalışma yılı, haftalık çalışma saati, sigara ve alkol kullanma durumu, gebelik, düşük ve küretaj sayısı, mevcut hastalık, ameliyat deneyimi, cinsel ilişki sıklığı, sürekli kullandığı ilaçlar, idrar kaçırma durumunu sorgulayan 27 soruyu içerdi.…”
unclassified